PERAN MANAJERIAL PENGELOLA DALAM MENINGKATKAN KOMPETENSI GURU DI SPS PAUD PELITA - Al Wahid, Salsabila Zalfa; Sutarjo, Sutarjo; Suminar, Uum (Comm-Edu (Community Education Journal), 2025)
This study examines how the managerial role of managers in improving the competence of teachers in SPS PAUD Pelita. The study used a qualitative descriptive approach, with data obtained through interviews with managers, teachers, and parents. The results show that managers contribute to the development of teachers through planning, direction, and involvement in External Training, although it has not been outlined in the form of official programs. Supporting factors include the commitment of managers, participation of parents, and cooperation with outside parties. The obstacles faced include limited funding, inadequate facilities, and the dual role of managers in school operations.